2020
DOI: 10.15275/rusomj.2020.0402
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Melatonin Secretion In Obese Adolescents With Or Without Obstructive Sleep Apnea

Abstract: Objective — To compare melatonin levels in saliva during a 24-hr day in order to identify the specificities of circadian melatonin secretion in obese adolescents with or without obstructive sleep apnea (OSA). Material and Methods — We examined 18 obese adolescents with OSA, 12 obese adolescents without OSA, and 15 healthy adolescents with a normal body weight, from whom saliva was sampled four time during the 24-hr day. Polysomnography was used to diagnose OSA. Saliva samples (n=180) were subjected to enzyme-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…One day prior to PSG, after the adolescents were enrolled in the study, saliva samples for measuring cortisol levels were collected from each participant four times over a 24-h period, namely, at 7:00 h (within 30 min of waking up), 13:00, 19:00, and 23:00 h [the author's technique for saliva collection was developed and applied by Madaeva et al ( 23 ) and tested on adolescents ( 9 )]. A sampling of saliva (4–5 ml) collected within 30 min after eating was avoided, and adolescents were told not to eat or drink milk products or sugary foods on the day of collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One day prior to PSG, after the adolescents were enrolled in the study, saliva samples for measuring cortisol levels were collected from each participant four times over a 24-h period, namely, at 7:00 h (within 30 min of waking up), 13:00, 19:00, and 23:00 h [the author's technique for saliva collection was developed and applied by Madaeva et al ( 23 ) and tested on adolescents ( 9 )]. A sampling of saliva (4–5 ml) collected within 30 min after eating was avoided, and adolescents were told not to eat or drink milk products or sugary foods on the day of collection.…”
Section: Methodsmentioning
confidence: 99%
“…Urinary measurements cannot reflect rapid diurnal changes in cortisol levels, and serial urinary sampling may be inconvenient for patients. In contrast, salivary sampling is a non-invasive and easy method that is more comfortable for patients and suitable for the measurement of diurnal cortisol (and some other biomarkers) in children and adolescents ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, changes in melatonin levels have also been evaluated to better understand changes in circadian biology in patients with OSA. Although, melatonin secretion is rhythmic in OSA patients [73] and may vary among patients with and without OSA [74], a significant number of studies have shown no changes in the rhythmic patterns of melatonin secretion/excretion or in response to dim-light onset among those with OSA compared to healthy controls [69,[75][76][77]. These studies suggest that hormones such as melatonin and cortisol are not preferable as circadian markers for the diagnosis and treatment of OSA.…”
Section: Physiological Rhythms In Osamentioning
confidence: 96%